PENGARUH RETURN ON ASSETS, DEBT TO EQUITY RATIO, PRICE TO BOOK VALUE, DAN FIRM SIZE TERHADAP RETURN SAHAM PADA SEKTOR TRANSPORTASI DAN LOGISTIK - Saraswati, Anisa Nia (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2025)
This study aims to analyze the effect of return on asset, debt to equity ratio, price to book value, and firm size on stock returns in the transportation and logistics sector. The population in this study were all 30 companies in the transportation and logistics sector. The sample used as many as 6 companies that are in accordance with the criteria set by the researcher. Sampling using purposive sampling method. The data source used is secondary data in the form of annual financial reports of transportation and logistics sector companies on the IDX in the 2016-2021 period. The research method used is casuality research using panel data regression through the Eviews program. In this study the results of a more precise model is the Common Effect Model. This study proves that return on assets have a positive significant effect on stock returns, price to book value have a positive significant effect on stock returns, and firm size have a positive significant effect on stock returns, while the debt to equity ratio has no effect on stock returns.